The coordinated action of PPR 4 and EMB 2654 on each intron half mediates trans ‐splicing of rps12 transcripts in plant chloroplasts - Kwanuk Lee; Su Jung Park; Catherine Colas des Francs‐Small; Michael Whitby; Ian Small; Hunseung Kang (2019)
The pentatricopeptide repeat proteins PPR4 and EMB2654 have been shown to be required for the trans-splicing of plastid rps12 transcripts in Zea mays (maize) and Arabidopsis, respectively, but their roles in this process are not well understood. We investigated the functions of the Arabidopsis and Oryza sativa (rice) orthologs of PPR4, designated AtPPR4 (At5g04810) and OsPPR4 (Os4g58780). Arabidopsis atppr4 and rice osppr4 mutants are embryo-lethal and seedling-lethal 3 weeks after germination, respectively, showing that PPR4 is essential in the development of both dicot and monocot plants. Artificial microRNA-mediated mutants of AtPPR4 displayed a specific defect in rps12 trans-splicing, with pale-green, yellowish or albino phenotypes, according to the degree of knock-down of AtPPR4 expression. Comparison of RNA footprints in atppr4 and emb2654 mutants showed a similar concordant loss of extensive footprints at the 3' end of intron 1a and at the 5' end of intron 1b in both cases. EMB2654 is known to bind within the footprint region in intron 1a and we show that AtPPR4 binds to the footprint region in intron 1b, via its PPR motifs. Binding of both PPR4 and EMB2654 is essential to juxtapose the two intron halves and to maintain the RNAs in a splicing-competent structure for the efficient trans-splicing of rps12 intron 1, which is crucial for chloroplast biogenesis and plant development. The similarity of EMB2654 and PPR4 orthologs and their respective binding sites across land plant phylogeny indicates that their coordinate function in rps12 trans-splicing has probably been conserved for 500 million years.